2016
DOI: 10.18295/squmj.2016.16.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tobacco-Specific Nitrosamines in the Common Smokeless Tobacco Afzal in Oman

Abstract: abstract:Objectives: There is a lack of awareness regarding the carcinogenicity of Afzal, an illegal smokeless tobacco product (STP) widely used among the Omani youth. Previous research has shown that certain types of tobacco-specific nitrosamines (TSNAs) are associated with oral and lung cancers. This study therefore aimed to assess levels of four common TSNAs in a randomly selected sample of Afzal. Methods: This study was carried out at Sultan Qaboos University in Muscat, Oman, between April and September 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…The similar conentration of Cd was found in Oman [37], Pakistan [28], and in India [33]. Chromium concentration was high in every tobacco product and is supported by the literature [28,33,[35], [36], [37]].
Fig.
…”
Section: Discussionsupporting
confidence: 79%
“…The similar conentration of Cd was found in Oman [37], Pakistan [28], and in India [33]. Chromium concentration was high in every tobacco product and is supported by the literature [28,33,[35], [36], [37]].
Fig.
…”
Section: Discussionsupporting
confidence: 79%
“…A recent study on snus Afzal from Oman showed that it exceeded the limits for N-Nitrosonornicotine (NNN) and 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) in tobacco products (Al-Mukhaini et al, 2016). The smokeless tobacco products produced in Russia, Sudan, and other Asian countries bear no information on compliance with the quality standards of those countries and the quality of refinement, which suggests that snus produced in these countries may contain other admixtures and have greater effect on oral health.…”
Section: Discussionmentioning
confidence: 99%
“…19 Quantities of Swedish snus are well monitored as they are typically sold in 1.00 g tea bag-sized sachets; 19 in contrast, Afzal users usually self-determine doses (typically a pinch-sized amount per single dose ranging from 1.00-2.00 g) which are then repeated as desired. 13 As a result, Cl -consumption will increase due to repeated Afzal use during the day. 16 Few studies have investigated the other anions tested in this study ( 4 2-(4,560.00-12,300.00 µg/g) and PO 4 2-(309.00-1,300.00 µg/g) levels in American STPs; their findings were higher than anion levels indicated in the current study (1,502.20 µg/g and 37.80 µg/g, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has determined the composition of heavy metals in Afzal. 13 The aim of this study was therefore to measure pH and moisture levels and assess cancer-causing agents in a random sample of Afzal.…”
mentioning
confidence: 99%